Radical Cystectomy and Cutaneous Ureterostomy in 4 Dogs with Trigonal Transitional Cell Carcinoma: Description of Technique and Case Series - Huppes, Rafael Ricardo; Crivellenti, Leandro Z. [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Lima, Bruno Roque; Cintra, Cristiane Alves; Costa Castro, Jorge Luiz; Adin, Christopher A. (Wiley-Blackwell, 2017)
Objective: To describe radical cystectomy followed by cutaneous ureterostomy as a treatment of invasive bladder neoplasia in dogs. Study Design: Retrospective study. Animals: Client-owned dogs with transitional cell carcinoma of the bladder trigone (n = 4). Methods: Perioperative complications and long-term outcomes of dogs that underwent cutaneous ureterostomy following radical cystectomy and lymphadenectomy for transitional cell carcinoma of the urinary bladder trigone were reviewed. Both ureters were transected and anastomosed to the ventral abdominal skin. Polyvinyl chloride catheters were placed in the ureteral stomas and maintained for 5 days. After catheter removal, dogs were managed with an absorbent diaper over the stomas. Long-term outcome and survival were documented by follow-up visits or phone contact. Results: Median age at the time of surgery was 10.3 years (range, 8-12). Average procedural time was similar to 4.7 hours (range, 3.8-6.1). Minor complications occurred in all dogs, including bleeding and edema of the ureterostomy site during the first 2-3 days after surgery. One dog developed urine scald that resolved with improved stoma care and hygiene. Median survival time after surgery was 278.6 days (range, 47498). Distant metastases were documented in 2 dogs at 47 days (bone) and 369 days (lung) after surgery. Conclusion: Radical cystectomy with cutaneous ureterostomy is a viable salvage procedure for urinary diversion after cystectomy in dogs with invasive bladder neoplasia. Postoperative management and quality of life were considered acceptable by most owners. Future studies are warranted to evaluate survival time in a larger number of animals.